Эрозия металлов под воздействием электрических разрядов - Куляпин, В.М. (Электрические контакты и электроды, 2010)
Совершенствование электротехнических комплексов и систем, как правило, сопровождается широким применением плазменных источников электронов и ионов различных видов разрядов (дуга, тлеющий разряд, полый катод и т. д.). Изложены результаты исследований взаимосвязанных теплофизических и эмиссионных процессов. Удосконалення електротехнічних комплексів та систем часто супроводжується широким застосуванням плазмових джерел електронів та йонів різних видів розрядів (дуга, тліючий розряд, полий катод та ін.). Викладено результати досліджень взаємопов’язаних теплофізичних та емісійних процесів. Improvement of electrotechnical complexes and systems is often accompanied by a wide use of electrons and ions of different dischargers ( arc, glow discharge, hollow cathode, etc) as a plasma source. Development of a theory of complex interconnected processes of thermionic emission as well as problems of non-standard heat conductivity with phase transformations and ablation due to evaporation are becoming increasingly important. All these processes occur in the potential drop region of high power concentration. The paper considers the processes of obtaining metal vapor with the help of electric discharges. Calculated erosion series rates that include relative coefficients of erosion bulk velocity (cm3/K), velocity of erosion per time unit (cm3/s) and mass of erosion velocity (g/s) were constructed.